Manejo de aceites lubricantes usados en las lubricadoras y lavadoras del cantón Buena Fe dentro de la cabecera cantonal San Jacinto de Buena Fe. - Zamora Ruiz, Darwin Xavier (2015)
The present research on the "Management of lubricating oils and washing machines in Canton Buena Fe lubricadoras within the cantonal head San Jacinto de Buena Fe" general objective, environmentally responsible planning, management of used lubricating oils in the lubricadoras and washing machines in Canton Buena Fe in the cantonal head. For which it met the following specific objectives: a diagnosis of the current situation of the management of used lubricating oils in establishments lubricadoras and washing was performed, a projection of the generation of used lubricating oils in terms of growth of the fleet was estimated A comprehensive management plan for lubricating oils generated in lubricadoras and washing machines in Canton Buena Fe in the cantonal head was proposed. To achieve these objectives visits were made to the lubricadoras to observe the handling is given to lubricating oils, surveys of owners lubricadoras were developed in order to determine whether the management of used oil is appropriate. The Excel 2010 software allowed for the screening of the generation of waste according to the growth of the fleet oils, for which data on the number of vehicles registered in the canton Buena Fe, data generation lubricating oils were collected in lubricadoras. The integrated management plan for lubricating oils generated in lubricadoras sets standards, characteristics and conditions for the management of used lubricating oils to run without damage to the environment, using appropriate techniques. This research will help people engaged in laundering activities and lubricated vehicles, which result lubricating oil used is generated, aware of the risk to health and the environment the lack of a comprehensive management plan for lubricating oils, and from that adopt innovative practices that positively contribute to the minimization of pollution.